Peningkatan Kemampuan dalam Menulis Puisi melalui Metode Bengkel Sastra Siswa Kelas VII SMP Negeri 14 Palu - Nayu, Marni (Bahasantodea, 2024)
The problem in this research was the students’ ability in writing poetry that aimed to describe the level of students ability through the literary workshop method with the stage of pre[1]writing, whilst-writing, and post-writing by the students of class VIII at SMP Negeri 14 Palu. This research was classroom action research, through this research, observation were conducted in order to enhance the students’ ability in writing poetry using literary workshop. The study design used the research design by Kemmis and MC. Tanggart. The research was coducted in 2 cycles covering every cycle consisted of planning, implementation, observation and reflection. The indicator of individual criteria of succes was 70% and classical criteria of succes was 75%. The aspects were assessed in writing the poem; object, diction, rhyme, figure of speech and mandate. The research results in the first cycle obtained 43,63% of individual achievement, and the classical achievement was 0%. In the second cycle, there were an increase in the average value of individual students of writing poetry reached 75,45% and 90,90% classical achievements. It could be concluded that learning by using the methods of literary workshop, the students’ ability of the grade VIII at SMP Negeri 14 Palu in writing poetry could be improved.